Biological aspect approach in sustainable management of coral catshark Atelomycterus marmoratus (Anonymous [Bennett], 1830) in Bali Strait, Indonesia - Tri Djoko Lelono; Gatut Bintoro; Ledhayane Ika Harlyan; Arief Setyanto; Mihrobi Khalwatu Rihmi; Didik Rudianto (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Lelono TD, Bintoro G, Harlyan LI, Setyanto A, Rihmi MK, Rudianto D. 2023. Biological aspect approach in sustainable management of coral catshark Atelomycterus marmoratus (Anonymous [Bennett], 1830) in Bali Strait, Indonesia. Biodiversitas 24: 5873-5882. Coral catshark (Atelomycterus marmoratus) is a shark species that thrives in many coral reefs. to evaluate the biological aspects of A. marmoratus and their type of growth curve for a time series to support their sustainability. Sampling was performed from August 23rd, 2019, to March 31st, 2020. The morphological analysis was performed by recording or photographing to reduce possible errors. Then, the length-weight relationship, sex ratio, length at first captured and matured, and spawning ratio were evaluated. The present study demonstrated that the coral catshark captured in the cohort that produces two cohorts only happens in February. The sex ratio is 41.6% male and 48.4% female, which is considered healthy, whereas the remaining percentage is so severely damaged that its gender cannot be determined. The FISAT-II software analysis results in a von Bertalanffy growth formula of Lt = 76.21 (1-e-2.01(t+0.0596)) with t max = 1.49/ year and L max = 77.39 cm. They grow steadily or tend to slow down after they reach the age of 1.5 years, with an asymptotic length of 77.39 cm. The Lc value (67.5 cm) is more significant than their Lm value (53 cm), indicating that their sustainability is highly possible to maintain because only fish that have passed the spawning stage are captivated. The spawning potential rate (SPR) is 35%, with M = 0.66, E = 1.85, and F = 0.78. These results indicate that the exploitation rate of coral catshark is moderate because 20% < SPR < 40%.  In conclusion, the A. marmoratus length-weight relationship is categorized as negative allometric, where the length grows faster than the weight.